La República de Venecia... (1617): «revenge» and parodical satyre of Boccalini’s Ragguagli di Parnaso. - Cappelli, Federica (Cuadernos de Filología Italiana, 2003)
This article is a portion of a bigger work which purposes to give an artistic revaluation to a kind of texts usually considered as para-literature. Hence, it intends to show, by the study of an anonimous Spanish libel structure and contents, its belonging to the «avvisi di Parnaso» genre, a type of literature easily useful both for seventeenth-century provenetians and pro-spanish, if handle with sharp parodical and satirical instruments.